Factors associated with mortality among paediatric tuberculosis patients in Blantyre and knowledge, attitudes and practice on tuberculosis transmission among parents and guardians of children with tuberculosis at Ndirande Health Centre in Blantyre, Malawi - Kishombe, Mable Cynthia (Kamuzu University of Health Sciences, 2022)
Although there is highly effective treatment, tuberculosis (TB) remains a leading cause of death in children. In 2018, 1.2 million deaths from TB among HIV-negative individuals and 251,000 deaths among HIV-positive people were estimated. Identifying patients at risk of death during TB treatment should be a priority for proper management. It helps in assessing the needs and identifying potential interventions that contributes to the End TB Strategy of reducing TB mortality by 95%. The study assesses factors associated with mortality amongst paediatric TB patients in Blantyre and knowledge, attitude and beliefs of TB disease transmission among parents/guardians of children. This was a cross-sectional study using retrospective records review of data extracted from Helse Nord Tuberculosis Initiative (HNTI) for different health facilities in Blantyre district and a primary data collection in assessing the knowledge, attitude and practice of the parents/guardians of children with TB and those with cough for more than a week at Ndirande Health Centre in Blantyre. The proportion of deaths was similar among males and females (5.1% compared to 5.6% respectively, with a P-value of 0.73). The death was higher among children of age group of 1 to 5 years with a death proportion of 6.9% compared to older children of 5-14 years (5.0%) although the results were not statistically significant P-value 0.374. Deaths numbers was higher among HIV positive children as 6.6% HIV positive children died comparing to 4.1 HIV negative patients who died with a P-value of 0.194. For the KAP study, parents/guardians had poor knowledge, attitudes and practices towards TB disease as of 150 participants interviewed in the primary data, 54.7% scored poor in knowledge, 68.7% had poor attitude and 22.0% displayed poor practices towards TB disease. There is a need to develop some effective techniques to educate the public on TB and improve the detection and management of tuberculosis in children.